Wpływ rezonansu stochastycznego na równowagę dziecka z Mózgowym Porażeniem Dziecięcym = Influence of stochastic resonance on body balance of children with Cerebral Palsy - Grzegorz Srokowski; Agnieszka Radzimińska; Magdalena Weber-Rajek; Zuzanna Piekorz; Marcin Siedlaczek; Agnieszka Jasionek; Anna Srokowska; Walery Zukow (Kazimierz Wielki University, 2015)
Srokowski Grzegorz, Radzimińska Agnieszka, Weber-Rajek Magdalena, Piekorz Zuzanna, Siedlaczek Marcin, Jasionek Agnieszka, Srokowska Anna, Zukow Walery. Wpływ rezonansu stochastycznego na równowagę dziecka z Mózgowym Porażeniem Dziecięcym = Influence of stochastic resonance on body balance of children with Cerebral Palsy. Journal of Education, Health and Sport. 2015;5(12):521-534. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.42266 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A521-534 http://pbn.nauka.gov.pl/works/686260 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 29.12.2015.   Wpływ rezonansu stochastycznego na równowagę dziecka z Mózgowym Porażeniem Dziecięcym Influence of stochastic resonance on body balance of children with Cerebral Palsy   Grzegorz Srokowski1, Agnieszka Radzimińska1, Magdalena Weber-Rajek1, Zuzanna Piekorz1, Marcin Siedlaczek1, Agnieszka Jasionek1, Anna Srokowska2, Walery Zukow3   • 1.      Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Techników 3, 85- 801 Bydgoszcz • 2.      Katedra i Zakład Podstaw Kultury Fizycznej, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85- 077 Bydgoszcz • 3.      Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska     Adres do korespondencji: Grzegorz Srokowski, Katedra Fizjoterapii Zakład Kinezyterapii i Masażu Leczniczego, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Techników 3 85 - 000 Bydgoszcz, g.srokowski@gmail.com Anna Srokowska, Katedra i Zakład Podstaw Kultury Fizycznej, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85- 077 Bydgoszcz, a.srokowska@cm.umk.pl   Streszczenie Wstęp: Mózgowe Porażenie Dziecięce MPD, jest to zespół chorobowy różnorodnych, niepostępujących zaburzeń Ośrodkowego Układu Nerwowego OUN. Objawiają się one poprzez zaburzenia czynności ruchowych i postawy. W konsekwencji dziecko poprzez brak możliwości sterowania w/w aktywnościami i brakiem kreowania odpowiednich reakcji posturalnych, zamienia je na reakcje obrony. Założenia i cel pracy: Przyjęto, że terapia polegająca na dostarczaniu organizmowi bodźców destabilizujących przez SRT - Zeptoring wpływa pozytywnie na reakcje równoważne i koordynację w czasie chodu. Celem pracy było zbadanie i ocena skuteczności terapii na urządzeniu SRT - Zeptoring zwanego Rezonansem Stochastycznym w grupie dzieci w wieku szkolnym ze stwierdzonym MPD. Metodyka: Badania zostały przeprowadzone w Ośrodku Rehabilitacyjnym " Neuron " Sp. Z o.o. w Małym Gacnie podczas trwania turnusu rehabilitacyjnego. Badaniami zostało objętych 15 osób,  były to dzieci i młodzież z różnymi typami MPD, poruszające się samodzielnie lub przy pomocy dodatkowego zaopatrzenia ortopedycznego. Badania obejmowały grupę testów funkcjonalnych, równoważnych oraz ocenę kontroli postawy ciała. Zostało wykonanych 10 treningów terapeutycznych na Rezonansie Stochastycznym, zgodnie z zasadami prowadzenia treningu na tym urządzeniu. Wyniki badań własnych: Szczegółowe wyniki przeprowadzonych badań przedstawiono w tabelach i zilustrowano wykresami. Wnioski: • Terapia za pomocą Rezonansu Stochastycznego wpływa pozytywnie na kontrolę postawy ciała. Jej konsekwencją jest poprawa funkcji równoważnych i kontroli chodu u dzieci z MPD. • Dzięki zastosowanej terapii polepszył się wynik końcowy w teście równowagi Tinetti, co oznacza zmniejszenie ryzyka upadku u dzieci z MPD.   Słowa klucze: fizjoterapia MPD, rezonans stochastyczny, chód, równowaga.     Abstract Introduction: Cerebral Palsy (CP) is an disease with different nonprogressive disorders of Central Nervous System (CNS). They manifest themselves through impairment of motor function and posture. As a result a child by the inability to control in this activities and lack of creation of appropriate postural responses turns them into defensive reactions. It was assumed, that therapy by providing the body with destabilizing stimuli by SRT - Zeptoring have positive impact on equivalent reactions and coordination during walking. The aim of the study was to examine and evaluate the effectiveness of the therapy on the SRT - Zeptoring device called Stochastic Resonance in a group of school children with diagnosed CP. Methods: The study was conducted at the Rehabilitation Center "Neuron" in Małe Gacno during the stationary rehabilitation. The study has covered 15 people, were children and young people with different types of MPD could move alone or with an additional orthopedic. The study included different functional tests, equivalent and an assessment of body postural control. 10 therapies were carried on Stochastic Resonance in accordance with the rules of conduct training on the machine. Results of the study: The detailed results of the study are presented in tables and illustrated on the graphs Conclusions: • Therapy using the stochastic resonance positively affects body posture control. The result is improvement of balance function and gait control in children with CP. • Thanks to the therapy patients has improved the end result of Tinetti balance test, which means a reduction in the risk of falling in children with CP.   Key words: physiotherapy CP, stochastic resonance, gait, balance.